2002
DOI: 10.1016/s0893-133x(02)00313-5
|View full text |Cite
|
Sign up to set email alerts
|

The Gerbil Elevated Plus-maze II Anxiolytic-like Effects of Selective Neurokinin NK1 Receptor Antagonists

Abstract: Neurokinin NK1 receptor antagonists may have therapeutic potential in the treatment of anxiety and depression. Species variants in the NK1 receptor result in reduced affinity 694,060,994,721 produced anxiolyticlike The tachykinin system, particularly the neurokinin NK1 receptor, may represent a new target for the treatment of a number of psychiatric disorders. Of greatest significance to the field, Kramer et al. (1998) described the anxiolytic and antidepressant effects of the NK1 antagonist, MK-869, in a 6-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 23 publications
(41 reference statements)
2
62
0
Order By: Relevance
“…Thus, the IC 50 for HEK 293 fibroblast cells was approximately three times higher than the IC 50 for tumor cells, 30 as occurring in the melanoma cell lines studied here. Indeed, in the host, aprepitant exerts beneficial effects in a dose-dependent manner, such as antiemetic, 29 antidepressant, 27 anxiolytic, 28 anti-inflammatory, 42 analgesic, 43 hepatoprotector 42 and neuroprotector. 44 In summary, we describe for the first time the presence of several isoforms of the NK-1 receptor in MEL HO, COLO 858 and COLO 679 human malignant melanoma cell lines.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the IC 50 for HEK 293 fibroblast cells was approximately three times higher than the IC 50 for tumor cells, 30 as occurring in the melanoma cell lines studied here. Indeed, in the host, aprepitant exerts beneficial effects in a dose-dependent manner, such as antiemetic, 29 antidepressant, 27 anxiolytic, 28 anti-inflammatory, 42 analgesic, 43 hepatoprotector 42 and neuroprotector. 44 In summary, we describe for the first time the presence of several isoforms of the NK-1 receptor in MEL HO, COLO 858 and COLO 679 human malignant melanoma cell lines.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Almentioning
confidence: 99%
“…Until now, this drug has been used as an antidepressant, anxiolytic and antiemetic. [27][28][29] Despite this, we have recently reported that aprepitant is a broad-spectrum antitumor drug. 30 However, to our knowledge, the presence of NK-1 receptors in melanomas and whether the antitumor action of the NK-1 receptor antagonist aprepitant is exerted on human malignant melanomas are unknown.…”
mentioning
confidence: 99%
“…60 min or 120 min (NK1 antagonists) before behavioral testing in a volume of 10 ml/kg body weight. Doses and pretreatment times were selected based on internally generated pharmacokinetic and pharmacodynamic data, as well as from previously published reports in which in vivo efficacy was demonstrated (Porsolt et al, 1977a, b;Varty et al, 2002bVarty et al, , 2003. Oral administration of compounds was used whenever possible in attempt to validate the model using the anticipated clinical route of administration.…”
Section: Drugsmentioning
confidence: 99%
“…To determine whether NK1 receptor antagonists would exhibit antidepressant-like effects in the gerbil FST, three prototypic compounds (eg MK-869, L-733060, CP-122721) that have previously been reported to exhibit behavioral effects (Duffy et al, 2002;Varty et al, 2002bVarty et al, , 2003 were tested in the gerbil forced swim and LMA tests. MK-869 (0.1-30 mg/kg) dose dependently reduced immobility times, with a minimum effective dose of 1 mg/kg (F(6, 93) ¼ 26.257; po0.05) (Figure 3a).…”
Section: Effects Of Nk1 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation